2002
DOI: 10.1097/00003246-200204001-00008
|View full text |Cite
|
Sign up to set email alerts
|

Arginine vasopressin during cardiopulmonary resuscitation: Laboratory evidence, clinical experience and recommendations, and a view to the future

Abstract: When stimulating adult pigs with ventricular fibrillation or postcountershock pulseless electrical activity for cardiopulmonary resuscitation, vasopressin improved vital organ blood flow, cerebral oxygen delivery, ability to be resuscitated, and neurologic recovery better than epinephrine. In pediatric preparations with asphyxia, epinephrine was superior to vasopressin, whereas in both pediatric pigs with ventricular fibrillation and adult porcine models with asphyxia, combinations of vasopressin and epinephri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
4

Year Published

2003
2003
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(11 citation statements)
references
References 36 publications
0
7
0
4
Order By: Relevance
“…Beta blockers may be preferred for ACSs if not already being taken. For pharmacological hemodynamic support during cardiac arrest management, vasopressin has been suggested as an alternative to epinephrine (344), but the evidence for superiority is not clearly established. Responses to nontachyarrhythmic cardiac arrest largely focus on control of metabolic and transient factors that may precipitate bradyarrhythmic events or pulseless electrical activity (Fig.…”
Section: Zipes Et Al Acc/aha/esc Practice Guidelines E413mentioning
confidence: 99%
“…Beta blockers may be preferred for ACSs if not already being taken. For pharmacological hemodynamic support during cardiac arrest management, vasopressin has been suggested as an alternative to epinephrine (344), but the evidence for superiority is not clearly established. Responses to nontachyarrhythmic cardiac arrest largely focus on control of metabolic and transient factors that may precipitate bradyarrhythmic events or pulseless electrical activity (Fig.…”
Section: Zipes Et Al Acc/aha/esc Practice Guidelines E413mentioning
confidence: 99%
“…Epinephrine and vasopressin may be used as an adjunct to defibrillation in an attempt to increase the coronary and cerebral perfusion pressure. 11 This dog received these recommended interventions and medications for CPR including monophasic defibrillation shocks at the recommended initial energy dose of 2-5 J/kg increasing to the maximal energy dose of 10 J/kg for patients 415 kg. 10 All attempts to reestablish normal circulatory function were unsuccessful until sinus rhythm was restored with a single biphasic shock.…”
Section: Discussionmentioning
confidence: 99%
“…It has the theoretical advantage over epinephrine of increasing oxygen delivery to vital organs without increasing oxygen consumption and worsening ischemia. [62][63][64][65][66] In cardiac arrest, the lack of perfusion causes anaerobic metabolism and lactate accumulation, quickly resulting in acidosis. In this hypoxic and acidotic state, adrenergic receptors become less sensitive to the vasoconstrictive effects of epinephrine and other catecholamines.…”
Section: Pharmacotherapymentioning
confidence: 99%
“…56,57 Vasopressin continues to cause vasoconstriction in the presence of acidosis. [62][63][64][65][66] In addition, studies have shown that increased epinephrine levels after cardiac arrest are associated with increased mortality, while increased levels of vasopressin are associated with improved survival. 67 A number of animal studies and early human trials found that the use of vasopressin in cardiac arrest improved ROSC, increased CPP, and improved neurologic outcomes.…”
Section: Pharmacotherapymentioning
confidence: 99%